Analisis Strategi Bauran Pemasaran Untuk Meningkatkan Volume Penjualan Sparepart Sepeda Motor pada CV Lembayung Persada Pekanbaru - Fajar Arsandy Hutama; Jushermi '; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study uses marketing science approaches, especially regarding the marketing mix strategy in increasing sales volume. As for the location of the research site is at the CV Lembayung Persada Pekanbaru. Sources of data used in this research is the documentation that researchers get the data directly from the data related CV Lembayung Persada Pekanbaru product, price, promotion costs and distribution costs. Based on the result of the study, in the variable product, it is known that in 2004 the type of products sold by CV Lembayung Persada Pekanbaru is a total of 12 items. However, in line with the types of items the business development of products sold has increased, until in 2013 CV Lembayung Persada Pekanbaru has been able to sell as many as 26 kinds of products Asamoto. At variable rates, for example, is the product of spare parts head light, CV Lembayung Persada Pekanbaru in 2009 to fix the price of Rp. 28.000, - and still the same price set in 2010. Though in 2011 the price of this product has increased by 10.71% or Rp. 31,000, - but this product still remains the choice of consumer confidence. In 2012, a decrease of -6.45% or Rp. 29.000, - as an effort to maintain the confidence and customer satisfaction to increase sales volume. The increase and decrease in the price of this happens in nearly all the price of products annually. In the variable cost of promotion, CV Lembayung Persada Pekanbaru only do efforts to provide discounts for new products. Improved high occurred in 2011 which reached 8.51%. This is because at this time the company launched two new products, and to attract customers, the company selling below the normal price for 3 months. In the variable distribution costs, it is known that in 2009 to 2010 the cost of distribution is only used for delivery in the city, and the total cost is only between Rp. 4.715 million, - up to Rp. 5.495 million, - but in 2011 a lot of demand for products for delivery outside the city such as West Sumatra and Jambi. Therefore distribution costs in 2011 increased by 23.52% or the total cost was Rp. 5.824 million for the purposes of distribution in the city and outside the city. It is suggested to the company to be able to maintain or even increase the interest of consumers to buy spare parts at CV Lembayung Persada Pekanbaru with attention to price and products.Keywords : Marketing Mix, Sales Volume.